Sustainable competitiveness as a new economic category – definition and measurement assessment - Cheba, Katarzyna; Bąk, Iwona; Szopik-Depczyńska, Katarzyna (Technological and Economic Development of Economy, 2020)
The main purpose of the paper is to assess the level of EU countries’ ability to compete in a sustainable manner and to compare these results with achievements in the area of sustainable competitive position. In the paper, the definition of the new economic category – sustainable competitiveness and its main components: sustainable competitive capacity and sustainable competitive position, as well as these new terms’ measurement proposal were presented. The study is also an attempt to the exploration of relationship existing between those categories. For this purpose, the selected statistical methods were applied. The taxonomic measure of development as well as the correlation coefficients, were used to measure the multilevel relationship between those considered areas. Until now, those categories were presented only in the context of examining the countries’ ability to compete sustainably. However, the aspects of sustainable competitive position have been completely ignored. That’s why it should be emphasized that this kind of investigation is a novelty in the area of sustainable competitiveness. The research results confirmed the existence of relationship between the various areas that consist to the holistic concept of sustainable competitiveness. These relationships are not always strong though and this is the crucial fact for further research in this area. First published online 1 October 2020